The effects of a plyometric training program on jump performance in collegiate figure skaters: A pilot study - Hunnicutt, J. L.; Elder, C. L.; Dawes, J. J.; Sinclair Elder, A. J. (International Journal of Exercise Science, 2016)
Plyometric training has been implemented to increase jump height in a variety of sports, but its effects have not been researched in figure skating. The purpose of this study was to determine the effects of a plyometric training program on on-ice and off-ice jump performance. Six collegiate figure skaters (19.8±1.2 years; 164.7±4.9 cm; 60.3±11.6 kg) completed a six-week sport-specific plyometric training program, consisting of low to moderate intensity plyometric exercises, while eight collegiate figure skaters (21.1±3.9 years; 162.6±6.0 cm; 60.4±6.1 kg) served as the control group. Significant increases were found for vertical jump height, standing long jump distance, (F = 31.0, p F = 11.6, p = 0.007). No significant differences were found for self-reported jump evaluation (p = 0.101). Six weeks of plyometric training improved both on-ice and off-ice jump performance in collegiate figure skaters, while short-term skating training alone resulted in decreases. These results indicate that figure skaters could participate in off-ice plyometric training.